2003
DOI: 10.3732/ajb.90.5.675
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and localization of short‐specific polygalacturonase in distylous Turnera subulata (Turneraceae)

Abstract: We describe for distylous Turnera subulata a polygalacturonase specific to short-styled plants that is localized to the style transmitting tissue (the tissue through which pollen tubes grow). The polygalacturonase gene is linked to and may be upregulated by the S allele of the distyly locus. Because of its tissue-specific location, the polygalacturonase may be involved in the self-incompatibility response, acting in a complementary or antagonistic manner, or possibly in signalling downstream events. A pollen-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(84 citation statements)
references
References 43 publications
4
80
0
Order By: Relevance
“…It has previously been shown that a style polygalacturonase and an a-dioxygenase display short-specific expression patterns and appear to be upregulated by the S-allele (Athanasiou et al, 2003;Khosravi et al, 2004;Tamari and Shore, 2004). Neither gene occurs in the vicinity of S-locus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been shown that a style polygalacturonase and an a-dioxygenase display short-specific expression patterns and appear to be upregulated by the S-allele (Athanasiou et al, 2003;Khosravi et al, 2004;Tamari and Shore, 2004). Neither gene occurs in the vicinity of S-locus.…”
Section: Discussionmentioning
confidence: 99%
“…We collected styles from newly opened flowers of each mutant as well as the parental plants (as controls). We then carried out sodium dodecylsulfatepolyacrylamide gel electrophoresis and immunoblotting to detect each of the proteins, following previous protocols (Athanasiou et al, 2003;Khosravi et al, 2004). Mutant SH1 flowers infrequently as many floral buds abscise before anthesis.…”
Section: Detection Of Polygalacturonase and A-dioxygenasementioning
confidence: 99%
See 1 more Smart Citation
“…Tamari et al (2001) suggested that this asymmetry could indicate that the morphs possess different self-incompatibility mechanisms. Athanasiou and Shore (1997) and Athanasiou et al (2003) provided evidence that proteins specific to the styles and pollen of short-styled plants of distylous Turnera scabra and T. subulata might be involved in distyly, possibly in the incompatibility system. Athanasiou et al (2003) showed that both proteins are polygalacturonases and that the style polygalacturonase is localized to the style-transmitting and stigmatic tissue.…”
Section: Introductionmentioning
confidence: 99%
“…There have been no convincing demonstrations of the occurrence of selfincompatibility proteins in any heterostylous species, although some efforts have been made in this direction (Golynskaya et al, 1976;Shivanna et al, 1981;Wong et al, 1994;Athanasiou and Shore, 1997). Turnera spp provide a useful system for identifying genes and proteins involved in distyly and self-incompatibility, given the relative ease and speed with which plants may be crossed and brought to flowering, and the increasing amount of work on distyly in this genus (Shore and Barrett, 1985;Barrett and Shore, 1987;Athanasiou and Shore, 1997;Tamari et al, 2001;Athanasiou et al, 2003). Distyly in Turnera scabra and T. subulata is determined by a single diallelic locus, where short-styled plants are heterozygous, Ss, and long-styled plants are homozygous, ss (Shore and Barrett, 1985).…”
Section: Introductionmentioning
confidence: 99%